Multilocus Sequence Typing of Staphylococcus aureus with DNA Array Technology - van Leeuwen, Willem B. (American Society for Microbiology, 2003)
A newly developed oligonucleotide array suited for multilocus sequence typing (MLST) of Staphylococcus aureus strains was analyzed with two strain collections in a two-center study. MLST allele identification for the first strain collection fully agreed with conventional strain typing. Analysis of strains from the second collection revealed that chip-defined MLST was concordant with conventional MLST. Array-mediated MLST data were reproducible, exchangeable, and epidemiologically concordant.